2020
DOI: 10.1111/andr.12791
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantification of coding and long non‐coding RNAs in stallion spermatozoa separated by density

Abstract: Background It is not unusual for stallions to have fertility problems. For many, artificial insemination with more dense spermatozoa (isolated by density gradient centrifugation) results in greater pregnancy rates compared with the rates when using unfractionated spermatozoa. RNAs in spermatozoa delivered to the oocyte at conception are required for embryo development. Novel molecular assays of spermatozoa that reflect function are needed to predict the fertility of stallions. Objectives To describe and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Targeting interferon regulatory factor 1 (IRF1) an, therefore, downregulating CCND1, cyclindependent kinase 2 (CDK2), and cyclin-dependent kinase inhibitor 1A, miR-383 controls mitotic division in spermatogonia and early spermatocytes (p21). 29,30 Additionally, SSCs express miR-294 and miR-295, while premeiotic male germ cells only express miR-201 and miR-547. 31 This suggests that these miRNAs regulate NOTCH, Erk1/2, and PI3K…”
Section: The Differentiation Of Male Sscs To Spermatocytesmentioning
confidence: 99%
“…Targeting interferon regulatory factor 1 (IRF1) an, therefore, downregulating CCND1, cyclindependent kinase 2 (CDK2), and cyclin-dependent kinase inhibitor 1A, miR-383 controls mitotic division in spermatogonia and early spermatocytes (p21). 29,30 Additionally, SSCs express miR-294 and miR-295, while premeiotic male germ cells only express miR-201 and miR-547. 31 This suggests that these miRNAs regulate NOTCH, Erk1/2, and PI3K…”
Section: The Differentiation Of Male Sscs To Spermatocytesmentioning
confidence: 99%
“…In large livestock, Wang et al [39] reported that lncRNAs are important in the regulation of bull sperm motility, and a total of 2517 lncRNAs were differentially expressed when compared between Holstein bulls with low or high sperm motility. In stallion sperm, 11,215 lncRNAs were identified, and 166 DELs were found to differ between groups of stallions living at greater and lower densities [40]. Because associations have been reported between many lncRNAs and reproductive disorders, it is very prudent to characterize and identify lncRNAs by sequencing and bioinformatic approaches as these may help us to determine the causes of male infertility [41].…”
Section: Introductionmentioning
confidence: 99%
“…The latter may thus, suggest the importance of spRNAs in regulating protein translation during spermatogenesis ( Bettegowda and Wilkinson, 2010 ). Comparative transcriptomics of stallion sperm identified 149 DE miRNAs between dense and less-dense spermatozoa ( Ing et al, 2020 ) wherein BC O 1, GLRA4, OTOL1, PRM1, SCP2D1 , and SPATA31D1 were highly expressed in dense spermatozoa compared to those of less-dense spermatozoa. This study also found that expression of PRM1 transcripts was significantly higher in morphologically normal spermatozoa from sub-fertile stallions and in spermatozoa with abnormal morphology ( Paradowska-Dogan et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many targets of spermatozoal lncRNAs have been predicted ( Gao et al, 2019 ) and were found to be enriched in apoptosis (e.g., PI3K-AKT, p53) ( Xiong et al, 2019 ) and capacitation-related pathways (e.g., Calcium, cAMP, and MAPK signaling) ( Gao et al, 2017 ). In stallion, comparative transcriptomics of dense and less-dense spermatozoa revealed 1,492 bp lncRNA as the most prevalent RNA ( Ing et al, 2020 ). Further, the expression of 159 RNAs was higher in dense spermatozoa than in less-dense spermatozoa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation